The 30th Sir Frederick Bartlett lecture. Fact, artefact, and myth about blindsight. - Cowey, A (2004)
Blindsight is the ability, still controversial if a vote is taken, of subjects with clinically blind field defects to detect, localize, and discriminate visual stimuli of which the subjects say they are completely unaware--the original definition--or of which they might be aware but not in the sense of experiencing a visual percept. These two conditions are known as blindsight Types I and II. This Bartlett lecture narrates the discovery of blindsight and its mounting opposition, and it evaluates the continuing and often perplexing debate about its standing as a visual cognitive phenomenon.